1999
DOI: 10.1021/jp983547x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Electrical Conduction in Organic Monolayer

Abstract: Electric conductivity of organic molecules was estimated with molecular resolution using self-assembled techniques and scanning tunneling microscopy (STM). Conjugated molecules of [1,1‘:4‘,1‘ ‘-terphenyl]-4-methanethiol (TP) were embedded in self-assembled monolayers of insulative n-alkanethiols, and when observed by STM, TP molecules appeared as protruding domains. The apparent height of the TP domains increases as the lateral size of the domains grows from 1 to 10 nm, reflecting the increase in the vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
148
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(163 citation statements)
references
References 28 publications
(57 reference statements)
14
148
1
Order By: Relevance
“…For SAMs formed from ͓1,1Ј;4Ј, 1Љ-terphenyl͔-4-methanethiol, a commensurate ͱ 3 ϫ 2 ͱ 3 structure, with an intermolecular spacing of about 5 Å, was observed by LEED and molecular resolution STM, 69 while a ͱ 3 ϫ ͱ 3R30°, with an intermolecular spacing again of about 5 Å, has been observed in other molecular resolution STM studies. 72,73 The band structure critical points might be reconciled to such a ͱ 3 ϫ ͱ 3 R30°hexagonal packing, if the band mapping is taken along the T line of the surface hexagonal Brillouin zone, toward the Brillouin zone edge ͑K ͒, but the second Brillouin center should not be observed in this case, so this structure remains difficult to reconcile with our data.…”
Section: Intermolecular Band Structurementioning
confidence: 71%
“…For SAMs formed from ͓1,1Ј;4Ј, 1Љ-terphenyl͔-4-methanethiol, a commensurate ͱ 3 ϫ 2 ͱ 3 structure, with an intermolecular spacing of about 5 Å, was observed by LEED and molecular resolution STM, 69 while a ͱ 3 ϫ ͱ 3R30°, with an intermolecular spacing again of about 5 Å, has been observed in other molecular resolution STM studies. 72,73 The band structure critical points might be reconciled to such a ͱ 3 ϫ ͱ 3 R30°hexagonal packing, if the band mapping is taken along the T line of the surface hexagonal Brillouin zone, toward the Brillouin zone edge ͑K ͒, but the second Brillouin center should not be observed in this case, so this structure remains difficult to reconcile with our data.…”
Section: Intermolecular Band Structurementioning
confidence: 71%
“…The lateral conductivity within highly ordered islands of the HBC thiolates embedded into a (non-conducting) 2D-matrix of an COMMUNICATION www.advmat.de alkanethiolate SAM was studied using the STM-based method proposed by Ishida et al [15] Whereas for a single molecule embedded in a matrix of insulating organothiolates only the direct (through bond) path leading from the STM tip through the molecule to the substrate exists, for a HBC thiolate embedded in a structurally well-defined island consisting of alike molecules the p-p coupling between adjacent molecules will allow for intermolecular charge transfer, thus opening additional current paths. This additional current will result in a larger conductivity, i.e., the molecule will appear higher in the STM micrographs.…”
mentioning
confidence: 99%
“…This additional current will result in a larger conductivity, i.e., the molecule will appear higher in the STM micrographs. [15] An analysis of the apparent height versus island size dependence allows to derive information on the charge transport between adjacent molecules. [16] The potential of this method has already been demonstrated for TP1-SAM islands embedded in a 2D-matrix of nonanethiolate or dodecanethiolate SAMs [15] and for C 11 -TTF-SAM islands embedded in a decanethiolate SAM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…STM and C-AFM, in conjunction with methods including use of Hg-drop electrodes, have been used as promising tools for studying the electrical conductance of molecules along the molecular axis [267,268], crossed wires [269], and break junctions [270,271]. As early as the late 90s, the conductance of single molecules embedded in insulating SAM films was discussed and evaluated by Bumm et al [237] and others [272][273][274][275][276], by use of STM. It was, however, shown that estimation of the electrical conductance of adsorbed molecules by use of STM is quite complicated compared with techniques in which the electrode is directly attached to the molecules [267][268][269][270][271].…”
Section: Self Assembled Monolayersmentioning
confidence: 99%